Financial Literacy of MSME Business Owners in the Municipality of San Jose, Negros Oriental, Philippines: A Basis for a State University’s Extension Program - Jaysone Christopher Bancoro (PT FORMOSA CENDEKIA GLOBAL, 2023)
Financial literacy is a crucial determinant of making sound and prudent financial decisions. However, a global study revealed that the majority of the world’s population is financially illiterate. From these precepts, this study was conducted to evaluate the level of financial literacy among 40 MSME business owners in the Municipality of San Jose, Negros Oriental, Philippines. The results will be used to decide if a university extension program could be started. This research made use of a descriptive methodology and collected data using five-point Likert scale survey method. The results of the study showed that MSME business owners have high levels of debt management, utilization of savings account, and reduce spending knowledge. On the other hand, MSME business owners need to improve in the overall personal financial management, long-term planning, emergency and risk. The researcher recommends the development of a comprehensive financial training program, sharing of best practices, and the provision of avenues for financial consultations. Improving financial literacy can help microbusiness owners better manage their finances, reduce financial stress, and increase the chances of their business's success